Gender aspects of personal and motivational sphere of students to physical education and sport - E.A. Bilichenko (Physical Education of Students)
Personal and motivational sphere of young men and women is studied. The study involved 210 students of Kremenchug National University (2 class - by 50 boys and girls, 4 class - by 30 people boys and girls, 25 people - athletes). Have external and internal factors affecting the particular relationship of boys and girls in physical education. Outline ways to increase motivation for physical education classes. Found that the organization of exercise can help to foster interest in these studies, the motivation for a healthy lifestyle. The limiting factors in the formation of motivation for physical activities are gender-specific value orientations of young boys and girls.